Cogset: a high performance MapReduce engine. (24th May 2012) - Valvåg, S.V.; Johansen, Dag; Kvalnes, Åge; Fedak, Gilles; Li, Keqiu; Lin, Kai
SUMMARY Cogset is a generic and efficient engine for reliable storage and parallel processing of distributed data sets. It supports a number of high‐level programming interfaces, including a MapReduce interface compatible with Hadoop. In this paper, we present Cogset's architecture and evaluate its performance as a MapReduce engine, comparing it with Hadoop. Our results show that Cogset generally outperforms Hadoop by a significant margin. We investigate the underlying causes of this difference in performance and demonstrate some relatively minor modifications that markedly improve Hadoop's performance, closing some of the gap. Copyright © 2012 John Wiley & Sons, Ltd.